Sistema de seguridad domiciliaria - Apolo Calle, José Luis (2009)
With the opening of the Security System’s Market there have arisen different types of systems, sensors and designs to provide safety to goods and areas inside which they interact. Many systems allow the user to have a visual access to their homes from any place using Internet like a way to access an image in real time in order to know the condition of the home. Having this in mind and the wide variety of existing systems and the facilities that they give us, we have developed an analysis of possible elements and sensors that we may use. Besides its location inside the home has been studied to offer a compatible design with any system that optimizes the monitoring and control of an environment reducing the number of used resources and the number of mistakes generated when selectingt between false and real alarms. This allows satisfactory results to user's needs. For this reason, we have developed a low cost Domiciliary Security System, scalable and with a high perfomance that gives users different levels of safety. Which increment in numbereach day and manintain a constant worry about the protection of homes and goods or anathing that could harm them. To implement this task there has been used the IMAQ Vision package of the LabVIEW 8.5 developed by National Instruments by means of whom it is possible to acquire images of two Web camera located in the environments to monitorear. LabVIEW 8.5 has been used working simultaneously with a MySQL Data Base. This allows the storage of the different alarms generated by the system. It is important to consider is that the system is totally autonomous and easily adaptable and it can be monitored locally or remotely thru the Internet.